Positioning for percutaneous nephrolithotomy. Issue 1 (January 2016) - Cracco, Cecilia Maria; Alken, Peter; Scoffone, Cesare Marco
Abstract : Purpose of the review: To highlight the progressive evolution of the issue of patient positioning for percutaneous nephrolithotomy (PNL), explain the history of the prone and supine positions, report respective advantages and drawbacks, critically interpret the past and current literature supporting such arguments, identify the best candidates for each position, and reflect on the future evolution of the two approaches. Recent findings: Positioning for PNL has become a matter of debate during the last decade. The traditional prone PNL position – most widely performed with good success and few complications, and exhibiting essentially no limits except for the treatment of pelvic kidneys – is nowadays flanked mainly by the supine and supine-modified positions, equally effective and probably safer from an anesthesiological point of view. Of course, both approaches have a number of advantages and drawbacks, accurately reported and critically sieved. Summary: The current challenge for endourologists is to be able to perform PNL in both prone and supine positions to perfectly tailor the procedure on any patient with any stone burden, including increasingly challenging cases and medically high-risk patients, according to the patient's best interest. Intensive training and experience is especially needed for supine PNL, still less popular and underperformed worldwide. Video abstract: http://links.lww.com/COU/A8 . Abstract : Supplemental Digital Content is available in the text